Productivity, earnings and composition of labour - irish-manufacturing-industries, 1953-1966 - Kennedy, Kieran A.; Dowling, Brendan R. (Economic & Social Studies, 1970)
In a paper read recently to the Statistical and Social Inquiry Society oflreland by one of the present authors,1 differences in the growth of labour productivity in Irish manufacturing industries over the period 1953 to 1966 were examined. It was found, amongst other things, that movements in output were highly correlated with movements both in labour input and in labour productivity; that there was only a small dispersion among industries in the movements of average labour earnings; and that movements in earnings were not highly correlated with movements in productivity. For the purposes of that paper the measure of labour input was simply numbers employed corrected for changes in hours worked. This paper examines the effect upon the findings when allowance is made, in measuring changes in labour input, for certain changes in the composition of the workforce in the period 1953-1966.
Keywords: Economics; Labour Productivity